Peran Kepolisian Daerah Jawa Tengah Dalam Penegakan Hukum Terhadap Tindak Pidana Judi Online - Nura Damayanti Ariningsih; Normalita Destyarini; Aryono Aryono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Information technology that is developing faster and faster encourages various aspects to develop as well, including crime. One of the crimes that follows the development of technology is gambling, in the past gambling was done conventionally in casinos or in stalls, now gambling can be done via the internet or what we often know as online gambling. This research aims to find out the efforts of the police in law enforcement against online gambling crimes and understand the procedures for handling cases of online gambling crimes at the Central Java Regional Police. This research is an empirical legal research using a legal sociological approach. The results of the study explain that in efforts to enforce the law on online gambling crime, the police apply preventive efforts through socialization, patrols in cyberspace, and cooperation with the Ministry of Communication and Information. Apart from preventive efforts, the police also apply repressive efforts with investigations and investigations. In this law enforcement effort, there are several inhibiting factors, including the lack of complete facilities and infrastructure and the vulnerability of securing evidence. The procedure for handling online gambling crimes is in accordance with the SOP, which includes police reports, investigations, investigations, arrests, searches, seizures, examinations, filing and the last is the submission of case files and defendants along with evidence to the public prosecutor.